Laser Dressed Magnetic Polaron In Semimagnetic Core/Shell Nanostructure. (23rd August 2021) - B., Anitha; Nithiananthi, P.
Abstract : The combined effects of magnetic and intense laser fields on the properties of the ground state exciton in semimagnetic Cd0.7 Mn0.3 Te/CdTe Core/Shell Nanostructure (CSN) are analyzed using the variational method in the effective mass approximation. The magnetic field of 5 to 20 T, a laser with the frequency of 10 THz and its intensity ranging from 0.44 to 7.11 μ W nm −2 are considered as external perturbing fields. The evolution of Exciton Magnetic Polaron (EMP) in response to the external fields is explored via Magnetization (M) and Zeeman energy shift (∆EZE ). The variation in binding energy (BE) of an exciton, M and ∆EZE are examined for different shell widths, magnetic and laser fields. The laser-induced diamagnetism due to the dressed energy state of carriers reduces the polarization of EMP. Similarly, the external magnetic field reduces the exchange interaction between carriers and weakens EMP. The combined effect of perturbing fields on an EMP will give an insight on controlling the performance of magneto-optic devices.